Pengaruh Pembiayaan Mudharabah, Musyarakah, Murabahah Dan Ijarah Terhadap Return On Equity (ROE) Pada Bank BCA Syariah - Devi, Yulistia; Ramadhan, Rudiansyah Dwi; Sari, Sherly Etika; Susanto, Is (Universitas Islam Negeri Raden Intan, 2022)
This study aims to determine the effect of mudharabah, musyarakah, murabahah and ijarah financing on return on equity (ROE). In this research, the approach used is associative research with saturated sampling technique. The data used is secondary data obtained from the quarterly financial statements of Bank BCA Syariah for 2010–2020. In this study using data analysis techniques, namely classical assumption test, multiple linear regression, t test, f test and coefficient of determination (R) with SPSS v 23 software. The results show that partially mudharabah, musyarakah and ijarah financing have no significant effect on ROE while murabahah financing has a positive and significant effect on ROE.